Hubungan Antara Kebiasaan Belajar dengan Hasil Belajar Biologi Pada Angkatan 2018 di UMMY Solok - Helvita Roza (Pendidikan Biologi FKIP UMMY, 2019)
This research is motivated by good study habits, including paying attention, noting essential things, doing assignments, having regular study time, and a high interest in learning. However, not all students have good study habits; many have difficulty understanding. Then, research will be conducted with the title